Research of New Sensorless Speed Controlled Drives with Induction Motors for Traction Applications - Vittek, Jan; Altus, Juraj; Bednarik, Bernard; Tabacek, Rastislav; Dodds, Stephen J.; Perryman, Roy (Communications - Scientific letters of the University of Zilina, 2001)
The research, aimed at an area of electric drives for electric traction, is based on a new approach to the speed control of electric drives employing induction motors without the aid of a shaft-mounted speed sensor. A novel feature of the proposed control system is that responses to the reference speed demand and the rotor magnetic flux norm reference input are mutually independent. The design control structure consists of an inner loop, which is a stator current control loop and outer loop, which is a shaft sensor-less speed control loop. A first order linear closed-loop response based on feedback linearization was chosen to derive basic control law. This original control law was later completed with other two control algorithms, which offer possibility of direct torque control with constant acceleration and control of speed and acceleration as it is prescribed with differential equation of the second order where acceleration fluently grows from zero to its maximum and then fluently decreases. To achieve sensorless speed control, the drive control system contains a set of three observers for estimation of the rotor magnetic flux, rotor speed and the load torque. Experimental results presented indicate good agreement with the theoretical predictions. The control system as developed to date would be suited very well to the applications requiring sensorless speed control with moderate accuracy ( 5 %). An interesting application area would be a new generation of low-cost controlled auxiliary drives for vehicles of electric traction which can mainly improve their reliability due to prescribed soft-start conditions. Also energy consumption of such kinds of auxiliary drives can be substantially decreased because they can easily and very efficiently accept changes connected with load conditions of the main drive.